2010
DOI: 10.1007/s11695-010-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Laparoscopic Adjustable Gastric Banding on Idiopathic Intracranial Hypertension

Abstract: The purpose of this study was to determine whether laparoscopic adjustable gastric banding has a role in the treatment of idiopathic intracranial hypertension. This pilot study was undertaken in a single, tertiary referral centre. Data on all patients with idiopathic intracranial hypertension that have undergone laparoscopic adjustable gastric banding in our unit were collected from our prospectively maintained bariatric database. Additional information was obtained via telephone questionnaires and review of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Interestingly, in morbidly obese IIH children with unsuccessful trials of weight loss, bariatric surgery can be considered with positive effects. This is also indicated if obesity is associated with other complications other than IIH, such as diabetes or sleep apneas (52,53).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Interestingly, in morbidly obese IIH children with unsuccessful trials of weight loss, bariatric surgery can be considered with positive effects. This is also indicated if obesity is associated with other complications other than IIH, such as diabetes or sleep apneas (52,53).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…When 4 female patients (mean BMI = 46.1) underwent laparoscopic adjustable gastric banding, with subsequent weight loss of 64.1% at follow-up, all 4 patients reported either total resolution or significant improvement in pain score. 59 However, larger randomized studies are not available at this time.…”
Section: Treatment Considerations For Overweight and Obese Headache Pmentioning
confidence: 99%
“…57,58 Surgical Weight Loss in IIH Patients.-As with migraine, there is some evidence supporting surgical weight loss for treatment of IIH. 59,60 When 19 severely obese women (mean BMI = 47) with IIH underwent bariatric surgery and were followed for 1 year, the mean BMI decreased to 30, and only 1 patient had persistent headache. 60 A more recent small clinical trial also showed promising results.…”
Section: Treatment Considerations For Overweight and Obese Headache Pmentioning
confidence: 99%
“…Four [20ā€“22, 25] of these were non-randomised prospective observation studies, and three [23, 24, 26] were retrospective case series. One study was subsequently excluded from quantitative synthesis due to lack of standard deviation data precluding further analysis.…”
Section: Introductionmentioning
confidence: 99%